PATIENT SAFETY CULTURE SURVEY IN THE SITI HAJAR ISLAMIC HOSPITAL - Pangastuti, Estry Mardhiah (Universitas Aisyah Pringsewu, 2024)
At trying to prevent unforeseen events, patient safety culture is crucial at healthcare facilities that provide care to patients. The high rate of reported deaths in some nations is a result of avoidable medical mistakes. According to information from the Ministry of Health of Indonesia, 12% of all Indonesian hospitals (RS) reported patient safety problems in 2019 having a rate of 5.2%, West Nusa Tenggara Province is Indonesia's 10th lowest prevalence of IKP in hospitals. Until March 2022, there were 4 cases at RSI Siti Hajar Mataram that happened in the medical support unit. This study's goal was to determine the patient safety culture at medical support unit. The research population for this study was the personnel of medical support units, and it used a cross-sectional research methodology with a total sample procedure. According to the analysis's findings, the following variables have a statistically significant impact on patient safety culture as a whole: perception, reporting frequency, supervision, communication openness, reciprocal error, staffing, and management support. Each dimension has a P value 0.05 and an average association strength that is both sufficient and strong. the requirement for more managerial involvement in the design, oversight, and evaluation of patient safety culture implementation.